Teaching fiberoptic-assisted tracheoscopy in very low birth weight infants: A randomized controlled simulator study - Wolf, Monika; Seiler, Berenike; Vogelsang, Valentina; Sydney Hopf, Luke; Moll-Koshrawi, Parisa; Vettorazzi, Eik; Ebenebe, Chinedu Ulrich; Singer, Dominique; Deindl, Philipp (Frontiers in Pediatrics, 2022)
Objective We developed a fiberoptic assisted tracheoscopy (FAST) method to avoid direct laryngoscopy during surfactant replacement therapy and compared two training approaches on a very low birth weight (VLBW) infant simulator. Design This prospective randomized controlled study was conducted at the Department of Neonatology and Pediatric Intensive Care Medicine of the University Medical Center Hamburg-Eppendorf, Germany. Participants We recruited physicians, trainees, students, and nurses without prior experience in endoscopic techniques. Interventions Participants were assigned randomly to a group that received instructions according to Peyton’s Four-Step Approach and a control group that received standard bedside teaching only. Main outcome measures Primary endpoints were the total and the component times required to place the bronchoscope and the method success. Results We recruited 186 participants. Compared to the control group, the Peyton group had a lower mean (±standard deviation) FAST completion time (33.2 ± 27.5 s vs. 79.5 ± 47.9 s, p < 0.001; d = 1.12) and higher FAST success rate (95% vs. 84%, p = 0.036, V = 0.18). Conclusions After standardized training, the vast majority of novices completed FAST successfully. Peyton's four-step approach resulted in faster and more successful performance than standardized training.